2022
DOI: 10.1093/g3journal/jkac239
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila FMRP controls miR-276-mediated regulation of nejire mRNA for space-filling dendrite development

Abstract: MicroRNAs (miRNAs) are enriched in neurons and play important roles in dendritic spine development and synaptic plasticity. miRNA activity is controlled by a wide range of RNA-binding proteins (RBPs). Fragile X mental retardation protein (FMRP), a highly conserved RBP, has been linked to miRNA-mediated gene regulation in axonal development and dendritic spine formation. FMRP also participates in dendritic arbor morphogenesis, but whether and how miRNAs contribute to its function in this process remains to be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that the expression level of miR-1 in peripheral blood of children suffering from acute-stage asthma positively correlated with interferon (IFN)-g expression and negatively correlated with disease severity (21). The metabolic balance of miR-276 determined the reproductive cycle of mosquitoes and the development of Plasmodium falciparum (22), and miR-276a played an important role in fragile X mental retardation protein (FMRP)-mediated spatial filling dendritic morphogenesis in Drosophila melanogaster (2). However, our study reported for the first time that miR-276-3p was highly expressed in the in-vitro model of allergic disease.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Previous studies have shown that the expression level of miR-1 in peripheral blood of children suffering from acute-stage asthma positively correlated with interferon (IFN)-g expression and negatively correlated with disease severity (21). The metabolic balance of miR-276 determined the reproductive cycle of mosquitoes and the development of Plasmodium falciparum (22), and miR-276a played an important role in fragile X mental retardation protein (FMRP)-mediated spatial filling dendritic morphogenesis in Drosophila melanogaster (2). However, our study reported for the first time that miR-276-3p was highly expressed in the in-vitro model of allergic disease.…”
Section: Discussionmentioning
confidence: 70%
“…House dust mites (HDMs) are one of the most important and most common indoor allergen sources worldwide that lead to asthma and other respiratory allergic diseases (1), and Dermatophagoides farinae (DFA) and D. pteronyssinus (DPT), two common species of HDMs, are widely prevalent in temperate and tropical regions (2,3). It is estimated that 65 to 130 million people worldwide are affected by HDMs allergy (3).…”
Section: Introductionmentioning
confidence: 99%